A change in the timing of the Bacillus Calmette–Guérin vaccination in 2013 was associated with an increase in the incidence rate of infants with latent tuberculosis infection. Issue 7 (July 2022) - Hino, Yumika; Eshima, Nobuoki; Tokumaru, Osamu; Bacal, Kira; Tanaka, Yuhei; Karukaya, Shigeru; Yamashita, Yushiro
Abstract: Background: A change in the timing of the Bacillus Calmette–Guérin (BCG) vaccination among infants in Japan appears to be associated with an increase in the incidence rate of latent tuberculosis infection (LTBI). Methods: Data on both active and latent tuberculosis (TB) infections from 2007 to 2019, which were reported by the Japan Anti-Tuberculosis Association, were statistically analyzed by comparing TB incidence rates in 2007–2012 and 2013–2019. Results: Although the incidence rate for active TB disease did not statistically increase nor decrease in the infant age group for either sex (and in fact decreased for some of the other age groups), the incidence rates of LTBI for both sexes were increased in the infant age group, while the incidence rates decreased in the other age groups. Between 2007 and 2012, the incidence rate of LTBI in females was statistically greater than those of males in the 1–4-year-old age group. From 2013 to 2019, the incidence rates of females were greater than those of males in both the infant and 1–4-year-old age groups, suggesting a growing preponderance of infections among female children in the youngest age groups. Conclusion: It may be that the change of BCG vaccination timing in Japan which took place in 2013 affected the infant incidence rate of LTBI, with a more prominent effect on females than males. In order to control TB infection, the ramifications of a change in vaccination timing therefore need careful exploration, as one such change appears associated with increased numbers of infants with LTBI, with disproportionate effects on females.